2021
DOI: 10.23887/ijll.v5i1.27694
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual Thematic Picture Dictionary: Assisting Young Learners’ Literacy

Abstract: This study aimed at developing a media, named a multilingual thematic picture dictionary to support the development of fourth grade elementary school students’ literacy. This study applied Design and Development research with Analysis, Design, Development, and Evaluation model proposed by Richey and Klein (2007). The subjects of the research were the fourth grade elementary school students who studied in rural and urban area. The data in this study were obtained from observation, interview, questionnaire, docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…It is consistent with Ratminingsih and Budasi (2019) that combining pictures, texts, and sound effects brought differences. It also corresponds with Wulandari et al (2021) that good literacy skills enable students to understand, create, and communicate information in oral or written form.…”
Section: Theory and Practice In Language Studiesmentioning
confidence: 89%
See 3 more Smart Citations
“…It is consistent with Ratminingsih and Budasi (2019) that combining pictures, texts, and sound effects brought differences. It also corresponds with Wulandari et al (2021) that good literacy skills enable students to understand, create, and communicate information in oral or written form.…”
Section: Theory and Practice In Language Studiesmentioning
confidence: 89%
“…Printed dictionaries are still needed, but digital dictionaries are easy and more flexible to use (Amirian & Heshmatifar, 2013). The most current study showed that a printed multilingual picture dictionary could assist young learners' literacy because it was developed based on the themes contained in the syllabus (Wulandari et al, 2021).…”
Section: Printed and Digital Dictionarymentioning
confidence: 96%
See 2 more Smart Citations
“…According to a study conducted by Wulandari et al (2021), dictionaries are a good media for accessing students' language skills. Taking the previous study, it may take utilization of technology also.…”
Section: Introductionmentioning
confidence: 99%